95.8k views
1 vote
Which polynomial is equivalent to (3z + 1)(z + 1)?

User Jimx
by
6.0k points

2 Answers

3 votes
3z^2 + 4z + 2
Believe this is correct
User Darren
by
6.7k points
3 votes

Answer:

3z^2 + 4z+1

Explanation:

(3z + 1)(z + 1)

we multiply it to get the polynomial

Apply FOIL method to multiply

Multiply 3z with z+1 first

3z *z = 3z^2

3z * 1 = 3z

Now multiply 1 with z+1

1*z= 1z

1*1= 1

Now we write all the terms together

3z^2 + 3z +1z +1

Combine like terms

3z^2 + 4z+1

User Sunghyun Cho
by
5.7k points